2003
DOI: 10.1093/emboj/cdg412
|View full text |Cite
|
Sign up to set email alerts
|

A signalling role for 4-hydroxy-2-nonenal in regulation of mitochondrial uncoupling

Abstract: Oxidative stress and mitochondrial dysfunction are associated with disease and aging. Oxidative stress results from overproduction of reactive oxygen species (ROS), often leading to peroxidation of membrane phospholipids and production of reactive aldehydes, particularly 4-hydroxy-2-nonenal. Mild uncoupling of oxidative phosphorylation protects by decreasing mitochondrial ROS production. We find that hydroxynonenal and structurally related compounds (such as trans-retinoic acid, trans-retinal and other 2-alken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
468
5
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(495 citation statements)
references
References 41 publications
17
468
5
5
Order By: Relevance
“…UCP3 is a mitochondrial inner membrane protein with unresolved physiological function(s). However, it has been hypothesised to mediate a proton leak when activated by HNE, reducing mitochondrial membrane potential and mitigating production of ROS in a negative feedback loop [39]. Interestingly, there were no differences in UCP3 expression between nondiabetic and post-diabetes mellitus participants under LGI conditions, but post-diabetes mellitus cells had lower expression of UCP3 at both the cellular and mitochondrial levels when exposed to HGI.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…UCP3 is a mitochondrial inner membrane protein with unresolved physiological function(s). However, it has been hypothesised to mediate a proton leak when activated by HNE, reducing mitochondrial membrane potential and mitigating production of ROS in a negative feedback loop [39]. Interestingly, there were no differences in UCP3 expression between nondiabetic and post-diabetes mellitus participants under LGI conditions, but post-diabetes mellitus cells had lower expression of UCP3 at both the cellular and mitochondrial levels when exposed to HGI.…”
Section: Discussionmentioning
confidence: 96%
“…4). It has been hypothesised that UCP3 may mitigate ROS production by uncoupling oxidative phosphorylation in situations of high membrane potential [37][38][39]. No overall differences in UCP3 protein content were observed between post-diabetes mellitus and non-diabetic myotubes under LGI conditions (Fig.…”
Section: 000mentioning
confidence: 92%
“…In fact, Echtay et al [28] also demonstrated that the uncoupling action of ANT as well as UCP was stimulated by 4-hydroxynonenal (HNE). It was also shown that knocking out one of two ANT isoenzymes (muscle-specific ANT1) results in a strong increase in ROS production by muscle mitochondria [29].…”
Section: Discussionmentioning
confidence: 99%
“…Modification of specific transcription factors, protein phosphatases or uncoupling proteins may affect the apoptotic threshold, the point of no return (such as the Bak-Bax gateway 12 ) or other RONS-mediated signaling effects on apoptosis 43 .…”
Section: Mitochondrial Rons Influence Cell Deathmentioning
confidence: 99%